Food Self-Sufficiency and Economic Growth in Southern Sumatra: An Empirical Analysis Using the Difference-in-Differences Method - Husaini, Muhammad; Purwaningsih, Vitriyani Tri; Hudani, Muhammad Mufti; Andrian, Thomas; Putra, Farid Azfa; Rozak, M. Ikhsan Nur (Jurnal Ekonomi Pembangunan, 2025)
This study examines the impact of the Gerakan Sumsel Mandiri Pangan (GSMP) program on regional economic growth in Southern Sumatra using a Difference-in-Differences (DiD) approach. GSMP is a flagship provincial program aimed at strengthening household food self-sufficiency and reducing dependence on social assistance. The analysis compares economic growth trends between South Sumatra Province as the treatment group and Lampung Province as the control group over the period 2019–2024. The DiD results indicate that, following the implementation of GSMP, the average growth of Gross Regional Domestic Product (GRDP) in the treatment province increased by approximately 0.024 percentage points relative to the control province. Further regression results show that food security, proxied by the Food Security Index, has a positive and statistically significant effect on GRDP, while population density exerts a negative influence. These findings imply that while GSMP contributes to improved food self-sufficiency and exhibits a positive association with economic growth, its aggregate impact on regional GRDP has not yet been sufficiently strong to generate statistically significant macroeconomic effects